Asymmetric information risk in FX markets - Ranaldo, Angelo; Somogyi, Fabricius (Journal of Financial Economics, 2021)
This work studies the information content of trades in the world’s largest over-the-counter (OTC) market, the foreign exchange (FX) market. It analyzes a novel, comprehensive order flow data set, distinguishing among different groups of market participants and covering a large cross-section of currency pairs. We find compelling evidence of heterogeneous superior information across agents, time, and currency pairs, consistent with the asymmetric information theory and OTC market fragmentation. A trading strategy based on the permanent price impact, capturing asymmetric information risk, generates high returns even after accounting for risk, transaction cost, and other common risk factors shown in the FX literature.